IMPLEMENTATION OF AUDIOVISUAL CENTERS IN GROUP B LEARNING AT TK ISLAM PLUS INSAN KAMIL TUBAN - Azkiyya, Chilyatul; Novitasari, Nurul; Rahman, Tatang Aulia (Al Hikmah Indonesian Journal of Early Childhood Islamic Education, 2024)
The implementation of the audiovisual center in learning is crucial for improving the quality of education at TK Islam Plus Insan Kamil Tuban. Therefore, this study aims to explain the implementation of the Audiovisual Center in Group B Learning at TK Islam Plus Insan Kamil Tuban. This research focuses on: 1) How do teachers implement the use of the audiovisual center in Group B learning at TK Islam Plus Insan Kamil Tuban? 2) What are the supporting and inhibiting factors in the use of audiovisual media in Group B learning at TK Islam Plus Insan Kamil Tuban? This research uses qualitative methods with data collection techniques including observation, interviews, and documentation. The results of this study show that: 1) the implementation of the audiovisual center is carried out well, and students at TK Islam Plus Insan Kamil Tuban have good skills in the audiovisual field. Teachers train students to try new things, take responsibility, be brave in asking questions, and express their imagination through creative works. The combination of engaging audiovisual media and positive psychological support from teachers creates an enjoyable and effective learning environment where students feel supported and motivated to learn. 2) the supporting factors for the use of audiovisual media in Group B learning include: a learning environment that provides access to technology, support from teachers and parents, a relevant curriculum, and creativity in learning. The inhibiting factors include: device malfunctions or software failures that can disrupt the smooth running of learning with audiovisual media.